2006
DOI: 10.1002/ts.61
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among cultural factors in microtuberization of white yam (Dioscorea rotundata)

Abstract: Single node cuttings from pathogen-tested in vitro plantlets of white guinea yam (D. rotundata), cultivar TDr 93-23, were cultured in tuberization and half-and full-strength Murashige and Skoog media with 5% or 8% sucrose, with or without agar, in light or darkness and at 25 or 18°C. Microtuberization is influenced by interactions among the factors, but 25°C and daylight are critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In the various Dioscorea species, different in vitro growth conditions have been reported as being optimum, mainly differing at the level of the carbon sources and growth regulator concentrations (Malaurie et al 1995a), and incubation conditions (Balogun et al 2006). We have shown that an increase of the sucrose concentration from 3% to 8% induced a significant increase of root (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In the various Dioscorea species, different in vitro growth conditions have been reported as being optimum, mainly differing at the level of the carbon sources and growth regulator concentrations (Malaurie et al 1995a), and incubation conditions (Balogun et al 2006). We have shown that an increase of the sucrose concentration from 3% to 8% induced a significant increase of root (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Growth of plantlets and tuberization in the third treatment were also significantly (P B 0.05) higher than in the first treatment (Table 1). Many plant species are easy to propagate in liquid medium compared to semi-solid or solid medium, which had been attributed to relatively ease of absorption of nutrients in the former (Balogun et al 2006). Yam clones ''Pacala Duclos'' and ''Belep'' in temporary immersion system also showed favorable results on shoot growth stage and in the development of microtubers in comparison with solid culture medium (Jova et al 2005).…”
Section: Resultsmentioning
confidence: 91%
“…and D. cayenensis Lam. (Viana and Mantell 1989), D. rotundata (Balogun et al 2006), D. nipponica Makino. (Chen et al 2007) and the D. cayenensis-D. rotundata complex (Ovono et al 2007(Ovono et al , 2009(Ovono et al , 2010a.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubers have a potential to be integrated into seed yam programs (Balogun et al, 2006;Chen et al, 2007). Microtubers are particularly convenient for handling, storage and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike micro propagated plantlets, they do not need a time consuming hardening period in a greenhouse and may be adapted easily to largescale mechanised planting in the field (Coleman et al, 2001;Pruski et al, 2003). Micro propagation of Dioscorea alata L. in semi-solid medium and in conventional size culture flasks is characterized by low microtuber formation frequencies by in vitro plants and microtubers with average fresh weight lower than 0.5 gFW (Balogun et al, 2006;Ondo et al, 2007;Balogun, 2009). These factors limit its use as propagule for propagation, microtuber formation and direct planting under field conditions.…”
Section: Introductionmentioning
confidence: 99%